Mode de dissemination des espèces les plus appetees par les elephants dans la zone Cynégétique de la Djona, les forets classees de Gouguon de la Sota et des environs, Nord-Benin - Aristide Tehou (Pachyderm)
Discusses habitat and wide range of vegetation elephants in the area eat and denotes their preferred foods as found from dung analysis in the Djona Hunting Zone in the dry Sudan zone of northern Benin. Suggests elephants are well adapted to various habitats in this area which range from almost desert conditions through savanna to forested areas, two of which the animals spend significant time, namely the Goungoun and Sota Notes there seems to be about 99 elephants in the area at present . Their feeding behaviour and species preference were observed directly, often photographed, and germination of plants in dung was noted. Two tables list the parts of 25 plant species which elephant consume during February to May and from June to January respectively.